2019
DOI: 10.12775/cjfa.2019.010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relative Impact of Monetary and Fiscal Policies on Economic Growth in Ethiopia, Using Ardl Approach to Co-Integration: Which Policy Is More Potent?

Abstract: Empirical investigation on the comparative potency of monetary and fiscal policies is still dubious among two major schools of thought in economics so called classical and Keynesian. Hence, this paper investigates the relative effectiveness of monetary and fiscal policies in affecting economic growth by employing Auto-Regressive Distributive Lag Model (ARDL) for the time spanning from 1975 to 2017. The proxies used in this study for monetary and fiscal policy were Broad money supply (M2) and govern-Tekilu Tade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This study fills the research gap by combining factors that affect economic growth and inflation, in previous studies only analyzing factors that affect economic growth (Akinwale & Grobler, 2019;Kallianiotis, 2019;Olamide et al, 2019a;Olamide et al, 2019b;Okoro et al, 2020;Solina & Ocampo, 2020) and inflation (Dua & Goel, 2021;Temitope, 2020;Tung, 2021) separately. In addition, this study uses panel data autoregression vector analysis, where previous research only focused on time series data analysis (Tadesse & Melaku, 2019;Tahir & Hayat, 2020;Tulasi, 2021) or panel data analysis (Younsi & Nafla, 2019;Okoro et al, 2020). This study will re-confirm whether the monetary policy stance through interest rates is the right instrument in maintaining price stability and encouraging economic growth, particularly in Indonesia, Malaysia, the Philippines, and Thailand.…”
Section: Introductionmentioning
confidence: 92%
“…This study fills the research gap by combining factors that affect economic growth and inflation, in previous studies only analyzing factors that affect economic growth (Akinwale & Grobler, 2019;Kallianiotis, 2019;Olamide et al, 2019a;Olamide et al, 2019b;Okoro et al, 2020;Solina & Ocampo, 2020) and inflation (Dua & Goel, 2021;Temitope, 2020;Tung, 2021) separately. In addition, this study uses panel data autoregression vector analysis, where previous research only focused on time series data analysis (Tadesse & Melaku, 2019;Tahir & Hayat, 2020;Tulasi, 2021) or panel data analysis (Younsi & Nafla, 2019;Okoro et al, 2020). This study will re-confirm whether the monetary policy stance through interest rates is the right instrument in maintaining price stability and encouraging economic growth, particularly in Indonesia, Malaysia, the Philippines, and Thailand.…”
Section: Introductionmentioning
confidence: 92%
“…Moayedi (2013) found that in Iran’s case, monetary policy is much less effective than fiscal policy in stimulating permanent economic growth and the findings were converse to what scholars found when examining Western countries. Tadesse and Melaku (2019) analysed the impact of monetary and fiscal policies on economic growth in Ethiopia. They found an empirically significant relationship between growth and monetary and fiscal policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have been investigated the impact of foreign aid on economic growth in Ethiopia, but they came up with mixed results. For example, studies by Tadesse (2011), Duresa (2022) and Girma and Tilahun (2022) found the positive relationship between foreign aid and the long-run economic growth, while other studies (e.g., Siraj, 2012;Haile, 2015;Kidanemariam, 2013;Gebru, 2015, andAbera, 2017) found the negative relationships between foreign aid and the longrun economic growth in Ethiopia. These mixed results lead to raise question of why impact of aid on economic growth in Ethiopia continues to be paradoxical in its findings.…”
Section: Introductionmentioning
confidence: 97%